Financial cost, salary and the impact towards coronary heart disease in Selangor / Mohamad Hafiz Rosli ...[et al.] - Rosli, Mohamad Hafiz; Mohamed, Juliza; Md Kassim, Aza Azlina; Zainal Azim, Zainal Azhar (Universiti Teknologi MARA, 2021)
Coronary heart disease (CHD) is one of the many non-communicable diseases (NCD). The World Health Organization (WHO) had reported that CHD has caused the death of 17.9 million people, representing 31% of global deaths. From this number, 85% are due to heart attacks and stroke. In Malaysia, CHD remained as the principal cause of death in 2018 with 18,627 deaths contributing to 15.6 percent of total deaths in Malaysia. Among the factors that could lead to CHD is hypertension. Chronic stress such as financial distress could lead to hypertension. Recently, the cost of living in Malaysia has increased significantly. This study intended to examine the impact of housing cost, transportation cost, self-education cost and salary towards CHD. The data was gathered by a survey questionnaire with 300 CHD respondents in Selangor. Multiple regression analysis was used for data analysis. The findings indicated that self-education costs and salary have significant a relationship with CHD. This research is expected to benefit policymakers in understanding the cost of living in Malaysia and to the public health department in their future policy and decision making processes on CHD prevention initiatives. Lastly, this study is expected to enrich the literature on CHD and cost of living.